In vitro models as tools for screening the relative bioavailabilities of provitamin A carotenoids in foods - Failla, Mark L.; Chitchumroonchokchai, Chureeporn (International Food Policy Research Institute, 2005)
This review is organized as follows. First, the characteristics of the digestion and absorption and the metabolism of vitamin A and carotenoids are briefly discussed in Sections 2 and 3, respectively. The numerous factors that affect carotenoid bioavailability are considered in Section 4. Section 5 first presents an overview of the techniques used to determine the relative bioavailabilities of carotenoids in vivo, and then describes the biochemical and cellular methods that are used to investigate the gastrointestinal processes associated with the accessibility and cellular transport of carotenoids. Key results from studies employing in vitro methods are systematically reviewed in Section 6. Finally Section 7 directly compares the findings of in vivo and in vitro studies and, on the basis of this comparison, proposes the use of simulated digestion and Caco-2 cells as tools for the initial screening for the relative bioavailability of provitamin A carotenoids from staple foods prepared according to local methods.